Photo- and thermo-induced changes in As-S-Se chalcogenide thin films - Bůžek, Jan; Pálka, Karel; Loghina, Liudmila; Vlček, Miroslav (Elsevier Science BV, 2017)
Compositional dependences of glass transition temperature T-g, optical properties and structure of AS(35)S(65-x)Se(x) thin films are studied in this paper. Changes of studied optical properties induced either by exposure to polychromatic light or annealing are also studied together with in-situ kinetics measurement. It was found that in comparison with annealing exposure to polychromatic light induces more significant changes in optical properties as a result of more significant internal structural changes which were confirmed by Raman spectroscopy.
Foto a termo indukované změny v tenkých vrstvách chalkogenidových skel systému As-S-Se
Keywords: Chalcogenide glasses; Photo-induced changes; Thermo-induced changes; chalkogenidová skla; foto-indukované změny; termo-indukované změny